Immunohistochemical identification of somatostatin and pancreatic polypeptide producing cells in pancreas of alpacas (Vicugna pacos) - Suni P., Nicanor (2018)
The aim of this study was to identify and evaluate gamma (PP) and delta cells in alpaca pancreas by immunohistochemistry (IHC). Samples were obtained from 30 alpacas from the southern highlands of Peru (crías, juveniles and adults). Histological sections of 5 μm thickness (3 per lobe and 2 of the body) were used. A commercial kit of IHC and polyclonal antibodies (anti-PP and anti-SSTR3) were used to identify PP and delta cells. Rat pancreas samples were used as positive controls. The intensity of the marking was qualitatively classified between 0 (no marking) and 3 (strong marking). PP cells were present in all age groups, mainly in the body and right lobe of the pancreas, being observed mainly in the periphery and intermediate zone of the islets with a medium and strong marking. Delta cells were present in both lobes until 4 months of age, without being observed in juveniles or adults. Delta cells were observed mainly on the periphery of the islets with a light marking.